Before and beyond Brexit: political dimensions of UK lifestyle migration. (29th March 2019) - MacClancy, Jeremy
Abstract: Lifestyle migration is a now‐established subfield within the anthropology of migration, and interdisciplinary migration studies, usually justified by its extensive and increasing spread, globally. Yet, bar a few exceptions, the political behaviour of lifestyle migrants has been relatively neglected. I redress this imbalance by critically comparing two overlapping processes where British migrants to Spain act politically: elected councillors in town halls; and campaigning anti‐Brexit activists. This pair is as comparable as it is contrastive. In theoretical terms, I argue that modern versions of practice theory are a useful mode for analysing municipal activity by foreign agents, while the Brexit process, because novel, fast‐paced, and open‐ended, is better understood via Isin's 'enactment of citizenship' approach. Both explanatory modes are powerful, have perspectival slants, and are best applied to different contexts and styles of contest: practice theorists research how people work with change; Isinians research how they produce it. The article also furthers the anthropology of citizenship by investigating a case where citizenship of a country is no longer a prerequisite for legitimate political activity in it.